Synthesis of Silica from Rice Husk Waste for Hydrophobic Material as an Anti-Water Coating for Eyeglasses - Phahul Zhemas Zul Nehan; Ahmad Ali Akbar; Muhammad Ilham Nur Karim; Raychan Abyqa Fahriza; Mochamad Zainuri (Jurnal Fisika dan Aplikasinya, 2023)
Hydrophobic materials made of silica as a coating for glasses are very attractive. The synthesis of silica (SiO2) from rice husk ash was successfully carried out using the sol-gel method. The hydrophobic silica composition is made with four variations of silica, consisting of 0.5, 1.0, 1.5, 2.0 g and polydimethylsiloxane (PDMS) keep constant in 20 g. The raw material was first characterized by X-ray Fluorescence (XRF) to investigate element composition. Then, silica powder obtained from rice husk ash was characterized by Fourier Transform Infrared Spectroscopy (FTIR), Particle Size Analyzer (PSA) and Water Contac Angel (WCA) were employed to investigate functional groups material, size of particles and hydrophobicity of the prepared samples for coating glass. The result of contact angel from coating glass exhibited more than 90◦ and the maximum hydrophobicity properties of polydimethylsiloxane/silica (PDMS/SiO2) was about 111.40◦ for the silica composition of 2 g.